High-Resolution Digital Elevation Modeling from TLS and UAV Campaign Reveals Structural Complexity at the 2014/2015 Holuhraun Eruption Site, Iceland - Müller, Daniel; Walter, Thomas R.; Schöpa, Anne; Witt, Tanja; Steinke, Bastian; Gudmundsson, Magnús T.; Dürig, Tobias (Frontiers in Earth Science, 2017)
Fissure eruptions are commonly linked to magma dikes at depth and are associated with elastic and inelastic surface deformation. Elastic deformation is well described by subsidence occurring above the dike plane and uplift and lateral widening occurring perpendicular to the dike plane. Inelastic deformation is associated with the formation of a graben, which is bordered by graben parallel faults that might express as sets of fractures at the surface. Additionally, secondary structures, such as push-ups, bends and step overs, yield information about the deforming domain. However, once these structures are formed during fissure eruptions, they are rarely preserved in nature, due to the effects of rapid erosion, sediment coverage or overprinting by other faulting events. Therefore, simple normal fault displacements are commonly assumed at dikes. At the 2014/2015 Holuhraun eruption sites (Iceland), increasing evidence suggests that developing fractures exhibited variations in their displacement modes. In an attempt to investigate these variations, a fieldwork mapping project combining Terrestrial Laser Scanning (TLS) and Unmanned Aerial Vehicle (UAV)-based aerophoto analysis was undertaken. Using these data, we generated local high-resolution Digital Elevation Models (DEMs) and a structural map that facilitated the identification of kinematic indicators and the assessment of the observed structures. We identified 315 fracture segments from these satellite data. We measured the strike directions of single segments, including the amount of opening and opening angles, which indicate that many of the measured fractures show transtensional dislocations. Of these, ~81% exhibit a significant left-lateral component and only ~17% exhibit a right-lateral component. Here, we demonstrate that the local complexities in these fracture traces and geometries are closely related to variations in their transtensional opening directions. Moreover, we identified local changes in fracture azimuths and offsets close to eruption sites, which we speculate are associated with geometric changes in the magma feeder itself. The results highlight that the opening of fractures associated with an erupting fissure may record transtensional modes with both, left-lateral and right-lateral components. These results further highlight the value of using UAV-based high-resolution data to contribute to the integrity of the observations of the structural complexities produced by local geologic events.